Augmenting the adsorption mechanisms in metal-organic frameworks via in Silico methods - Borzehandani, Mostafa Yousefzadeh (2023)
Metal-organic frameworks (MOFs), intricate structures composed of organic linkers and metal nodes, exhibit remarkable versatility with applications ranging from gas adsorption and separation to drug and energy storage, water absorption, and catalysis. Despite their broad utility, a comprehensive understanding of the factors influencing adsorption within MOFs is essential for optimizing their potential as adsorbents. This study systematically categorizes and investigates various factors through computer simulations, shedding light on their nuanced effects. The first focus centers on the functionalization of IRMOF-74-III with amine groups, a critical aspect of enhancing drug adsorption. The exploration delves into the impact of different numbers and positions of amine functional groups on the MOF's behavior, utilizing density functional theory (DFT) and molecular docking. As the number of amine group increases, the MOF's pore polar surface area expands, but a reduction in the energy gap between the HOMO and LUMO orbitals is observed. Electrostatic potential contours reveal distinct pockets on the amine-functionalized IRMOF-74-III's pore wall, which fenbufen@MOF showing the most stable drug@MOF complex. The study emphasizes the crucial role of unsaturated magnesium sites in frameworks and specific functional groups on drugs for interactions and charge transfer. The second exploration addresses MOFs' ability to selectively adsorb isomers, as exemplified by MIL-53(Al) MOF's adsorption of xylene isomers. The introduction of non-polar functional groups on the organic linker was proposed for enhanced adsorption. Computational analysis of different configurations of dimethyl-functionalized phenyl rings reveals meta-dimethyl- MIL-53(Al) (MDM) as an optimal structure for xylene adsorption, demonstrating superior adsorptive separation of ortho- over meta- and para-xylene. The third study introduces an innovative alternative to MOF functionalization by directly replacing the organic linker with a structurally similar compound, preserving the framework topology. Using computer simulations, the impact of replacing the organic linker in HKUST-1 MOF with borazine is analyzed. Borazine-based HKUST-1(Cu) (hB-HKUST-1(Cu)) exhibits a significant improvement in CO2 adsorption compared to the conventional